Undignifying institutions. Issue 6 (1st December 2002) - Seedhouse, D; Gallagher, A
Abstract : Declarations of the importance of dignity in health care are commonplace in codes of practice and other mission statements, yet these documents never clarify dignity's meaning. Their vague aspirations are compared to comments from staff and patients about opportunities for and barriers against the promotion of dignity in elderly care institutions. These suggest that while nurses and health care assistants have an intuitive understanding of dignity, they either do not or cannot always bring it about in practice. Thus, despite stated intentions to promote dignity, it appears that the circumstances of at least some elderly care institutions cause patients to experience avoidable indignities. Such institutions are "undignifying institutions" because they fail to acknowledge dignity's basic components, focus excessively on quantifiable priorities, and have insufficient resources available to assure consistently dignifying care. As a partial solution, we argue that health workers should be taught to understand and specify the components of dignity, which will better prepare them to challenge undignifying practices and to recognise opportunities for dignity promotion.